Risk Factors for Illness Severity Among Pregnant Women With Confirmed Severe Acute Respiratory Syndrome Coronavirus 2 Infection—Surveillance for Emerging Threats to Mothers and Babies Network, 22 State, Local, and Territorial Health Departments, 29 March 2020–5 March 2021. (22nd May 2021) - Galang, Romeo R; Newton, Suzanne M; Woodworth, Kate R; Griffin, Isabel; Oduyebo, Titilope; Sancken, Christina L; Olsen, Emily O'Malley; Aveni, Kathryn; Wingate, Heather; Shephard, Hanna; Fussman, Chris; Alaali, Zahra S; et al.
Abstract: Background: Pregnant women with coronavirus disease 2019 (COVID-19) are at increased risk for severe illness compared with nonpregnant women. Data to assess risk factors for illness severity among pregnant women with COVID-19 are limited. This study aimed to determine risk factors associated with COVID-19 illness severity among pregnant women with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Methods: Pregnant women with SARS-CoV-2 infection confirmed by molecular testing were reported during 29 March 2020–5 March 2021 through the Surveillance for Emerging Threats to Mothers and Babies Network (SET-NET). Criteria for illness severity (asymptomatic, mild, moderate-to-severe, or critical) were adapted from National Institutes of Health and World Health Organization criteria. Crude and adjusted risk ratios for moderate-to-severe or critical COVID-19 illness were calculated for selected demographic and clinical characteristics. Results: Among 7950 pregnant women with SARS-CoV-2 infection, moderate-to-severe or critical COVID-19 illness was associated with age 25 years and older, healthcare occupation, prepregnancy obesity, chronic lung disease, chronic hypertension, and pregestational diabetes mellitus. Risk of moderate-to-severe or critical illness increased with the number of underlying medical or pregnancy-related conditions. Conclusions: Older age and having underlying medical conditions were associated with increased risk of moderate-to-severe or critical COVID-19 illness among pregnant women. This information might help pregnant women understand their risk for moderate-to-severe or critical COVID-19 illness and can inform targeted public health messaging.